Who is afraid of electric vehicles? An analysis of stated EV preferences in Switzerland - Jeremy Van Dijk; Mehdi Farsi (University of Neuchâtel, Institute of Economic Research (IRENE), 2022)
We provide novel evidence for the size of key electric vehicle (EV) adoption barriers, purchase price and battery range, and the driver, operating cost, in the broadening EV market. We further demonstrate the heterogeneity of these across consumer segments, plus determine groups most resistant to EV adoption and the relationship with transport habits and car ownership. To this end we analyse the results of a choice experiment of 882 respondents across Switzerland, a market that has favourable adoption criteria, however realises a low EV market share. We find low and inelastic elasticities of price, range and driving cost, and high variation across levels of urbanisation, income and car ownership. We additionally see high technological preference inertia among car owners, and a larger probability of non-owners and public transport users to choose EVs. We finally propose targeting EV adoption policies to relatively sensitive consumer groups to maximise efficiency, and support alternative policies to overcome low overall elasticities and achieve greater effectiveness.
Keywords: D90; O33; Q40; Q48; Q50; Q58; R40; 330; Transport; Electric vehicles; Adoption; Choice experiment; Stated preferences; Environmental policy; Behaviour